The Development of the First Nations Children Wellbeing Measure - Drawson, Alexandra S.; Toombs, Elaine; Blain, Jay; Bobinski, Tina; Dixon, John; Paavola, Natalie; Mushquash, Christopher J. (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objectives: The overall goal of this project was to implement a measurement tool intended to assess the wellbeing of First Nations children within the Robinson Superior Treaty Area. Methods: A community-based participatory research approach was utilized, which included a research advisory composed to employees from the organization that was partnered with. Both interviews and focus groups were held with members of the communities within the Robinson Superior Treaty Area, and the content of these was examined to determine indicators of wellbeing for children in these communities. The indicators that arose from this analysis made up the pilot version of the measure, which was administered to the parents or caregivers of children (n = 91) who were seen through the intake service for the organization. They were also administered the Child and Adolescent Needs and Strengths measure (Lyons et al., 1999). Results: A principal components analysis was performed, which yielded three factors: (1) General Wellbeing, (2) Traditional Activities, and (3) Social Engagement. Discussion: Involvement in traditional activities and engagement in culture were cited as fundamental indicators of wellbeing of First Nations children, which is consistent with the majority of the literature. The instrument that was created and evaluated represents one of few valid tools available to assess this. Implications: The measure and process of creating this measure contributes to the literature on the significance of traditional activities for the wellbeing of Indigenous people.